Economic importance of the Flemish maritime ports: Report 2002 - Frédéric Lagneaux (National Bank of Belgium, 2004)
This paper provides an extensive overview of the economic importance and development of the Flemish maritime ports, over the period 1995 - 2002. Focusing on the three major variables of value added, employment and investment, it also provides some information about the financial situation of a few vital segments in each port. In addition, it includes figures with respect to the ongoing growth of several cargo traffic segments and attempts to establish a link between these and the progress of the production in the industries at stake. The breakthrough of this research - compared to its previous editions - consists of evaluating the indirect effects of the sectors in question in terms of value added and employment. A few refinements have also been made, such as the routine geographical and functional selection of companies according to the cluster they belong to (NACE-Bel code pproach), the limitation of administrative work incurred, the review of the companysize nalysis, etc. Annual reports data from the Central Balance Sheet have been computed for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. For the estimation of indirect effects, Supply and Use Tables from the National Accounts Institute have been resorted to. The developments in the maritime ports sector are numerous nowadays, namely in the Hamburg - Le Havre range: concentration of capital, privatization of ports logistics services, expansion and dispersion of foreign trade, the internationalization of the production and consumption patterns (e.g. increase in containerized shipments), the latest requirements of world trade concerning transport and distribution. The increase in scale and specialization of the vessels inevitably impact on the operation of the ports. Production, trade and transport are not longer considered as individual, isolated activities, but are integrated in a single system. Therefore, ports have to evolve from mere centres of transport (discharging and loading of vessels) to logistics centres. Moreover, ports able to add value to the goods passing through the port area, have a major asset in a climate of increasing international competition. These developments are also mentioned in this report, since no Flemish port is an exception to this rule.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport intermodality; public investments; Hafen; Branchenentwicklung; Flandern; Wirkungsanalyse